Mitral regurgitation severity correlates with symptoms and extent of left atrial dysfunction: Effect of mitral valve repair. Issue 1 (26th September 2017) - Lisi, Matteo; Cameli, Matteo; Di Tommaso, Cristina; Curci, Valeria; Reccia, Rosanna; D'ascenzi, Flavio; Focardi, Marta; Maccherini, Massimo; Chiavarelli, Mario; Lisi, Gianfranco; Lindqvist, Per; Mondillo, Sergio; et al.
Abstract: Purpose: We aimed to assess the relationship between mitral regurgitation (MR) severity, symptoms, and left atrial (LA) structure and function, before and after mitral valve repair (MVR). Methods: Global peak atrial longitudinal strain (PALS) was evaluated in 37 patients with severe symptomatic MR and preserved left ventricular (LV) ejection fraction (60.4% ± 4.6%) before and 3 months after MVR and was compared with values from 30 age‐ and gender‐matched controls. Results: Before surgery, PALS was worse in patients than in controls and indexed LA volume was greater ( P  < .0001 for both). After MVR, PALS deteriorated further and LA volume decreased ( P  = .001 and P  = .05, respectively) as did LV ejection fraction, longitudinal strain ( P  = .05 and P  < .001, respectively), and LV mass ( P  < .0001). Before surgery, LA volume correlated modestly with LV end‐diastolic volume ( R  = 0.51; P  = .01); effective regurgitant orifice area (EROA) correlated with PALS ( R  = −0.69, P  < .001) and with LV longitudinal strain ( R  = 0.54, P  = .01), and New York Heart Association class correlated with PALS ( R  = −0.69, P  < .001), EROA ( R  = 0.69, P  < .001), and LA volume ( R  = 0.51, P  = .04). LA volume was the strongest predictor of global PALS reduction ( P  < .001), whereas global PALS was the main predictor of postoperative atrial fibrillation (AF) ( P  < .001). Conclusions: In patients with severe MR, EROA correlate with symptoms and LA PALS, which itself predicts the occurrence of postoperative AF. Strain values were superior to 2D data for the prediction of postoperative AF.